2012
DOI: 10.1016/j.otsr.2012.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Operative treatment of clavicle midshaft fractures using a locking compression plate: Comparison between mini-invasive plate osteosynthesis (MIPPO) technique and conventional open reduction

Abstract: Level IV. Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 32 publications
5
47
0
10
Order By: Relevance
“…Fifteen of these studies proved eligible for inclusion ( Figure 1). 5,10,[30][31][32][33][34][35][36][37][38][39][40][41][42] The overall agreement between the 2 reviewers for final eligibility was excellent (κ value = 0.94, 95% confidence interval [CI] 0.84-1). All 15 studies were published between 2007 and 2013; their characteristics are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen of these studies proved eligible for inclusion ( Figure 1). 5,10,[30][31][32][33][34][35][36][37][38][39][40][41][42] The overall agreement between the 2 reviewers for final eligibility was excellent (κ value = 0.94, 95% confidence interval [CI] 0.84-1). All 15 studies were published between 2007 and 2013; their characteristics are summarized in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…43 Five studies compared different operative implants. [37][38][39][40][41] One placebo-controlled trial managed all fractures nonoperatively. 42 Twelve studies were reported in English.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25][26] Minimally invasive percutaneous plate osteosynthesis technique along with application of a locking plate has been recently introduced, offering an ideal combination in terms of bone fixation and soft-tissue sparing since periosteal stripping can be minimized to promote rapid union. 6,27) In this study, fractures were treated with an anatomical plate or locking plate, and union was achieved in all cases. We prefer open reduction and internal fixation over minimally invasive techniques since they allow for ease of access to the fracture site and precise reduction of complex fractures.…”
Section: Discussionmentioning
confidence: 99%
“…5) Treatment options for acute mid-shaft clavicle fractures include open reduction and internal fixation with plates as well as closed or open reduction and internal fixation with intramedullary (IM) pins, wires, or a nail. [6][7][8] Advantages of plate fixation are anatomical reduction, which enables immediate stabilization. Although high success rates of plate fixation have been achieved, reported complications of plate fixation include implant failure, implant prominence, nonunion as a result of extended periosteal stripping, and soft tissue damage.…”
Section: Introductionmentioning
confidence: 99%